Therapeutic Nanomaterials: Microphysiological Systems: Next Generation Systems for Assessing Toxicity and Therapeutic Effects of Nanomaterials (Small Methods 1/2020). Issue 1 (9th January 2020) - Ashammakhi, Nureddin; Darabi, Mohammad Ali; Çelebi‐Saltik, Betül; Tutar, Rumeysa; Hartel, Martin C.; Lee, Junmin; Hussein, Saber M.; Goudie, Marcus J.; Cornelius, Mercedes Brianna; Dokmeci, Mehmet R.; Khademhosseini, Ali
Abstract : Microphysiological systems, also known as organ‐on‐a‐chip platforms, are increasingly poised to replace costly animal studies. The utilization of integrated multiorgan‐on‐a‐chip systems for advancing nanotechnology will be reflected in future drug development, toxicology studies, and precision medicine. In article number 1900589 by Nureddin Ashammakhi, Ali Khademhosseini, and co‐workers, various aspects of related studies, current challenges, and future perspectives are discussed.